Biological determinants of physical activity differentiation for women of the first mature age (aged 21 to 35) who do water fitness - Anna Tkachova; Nataliia Goncharova; Tetyana Prylutsʹka (Kazimierz Wielki University, 2017)
The article highlights the problems of organization and conduct of health fitness classes for women of mature age on the basis of theoretical analysis and practical experience. The high level of social significance of systematic health fitness training for women aged 21 to 35 is defined, the favorable influence of physical culture and health classes on the body of women of reproductive age is outlined. The purpose of the study was to determine the indicators impact on which will enable optimization of health water fitness classes for women aged 21 to 35 based on factor analysis of physical development and physical preparation in women of the first mature age. Among the research methods used analysis of scientific and methodological literature, systematization, anthropometric research methods, methods of mathematical statistics were applied. During the study 46 women of the first mature age who do water fitness were involved. The participants of the study confirmed their consent to participate in the pedagogical experiment in writing. The factor structure of physical development, physical preparation and motor activity in women of the first mature age was defined, which allowed to create a representation regarding the list of informative indicators that have the most significant influence on other indicators. Among the informative indicators in the factor structure of physical development, physical preparation and motor activity of women, the leading factor is determined by the physical preparation of women, namely the functional state of the musculoskeletal system. Among the significant indicators, the leading positions are also occupied by the component composition of the body (fat component) and the type of women physique, considering the existing disorders of neutral spine as a direction of influence during classes. The correlation of means of physical training that will optimize water fitness classes for women of the first mature age is determined.